1998
DOI: 10.1038/bjc.1998.375
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin vs epirubicin, report of a second-line randomized phase II/III study in advanced breast cancer

Abstract: Summary The EORTC Breast Cancer Cooperative Group carried out a randomized trial to compare doxorubicin with epirubicin as secondline chemotherapy in patients with metastatic breast cancer. Two hundred and fifty-nine patients with at least one site of metastatic disease entered this trial, of whom 232 patients were eligible. Treatment consisted of doxorubicin 75 mg m-2 or epirubicin 90 mg m-2 i.v. every 3 weeks. The overall response rates for doxorubicin and epirubicin were 36% and 28% respectively (P = 0.173)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Several single-agent chemotherapeutic options have been shown to be effective as first-or second-line therapy, with taxanes and anthracyclines being among the most effective [13][14][15][16][17][18][19]. After treatment with an anthracycline or taxane, administration of capecitabine, gemcitabine, and vinorelbine have been found to result in OR rates of 20-25% (Table 2) [20][21][22].…”
Section: Single-agent Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Several single-agent chemotherapeutic options have been shown to be effective as first-or second-line therapy, with taxanes and anthracyclines being among the most effective [13][14][15][16][17][18][19]. After treatment with an anthracycline or taxane, administration of capecitabine, gemcitabine, and vinorelbine have been found to result in OR rates of 20-25% (Table 2) [20][21][22].…”
Section: Single-agent Chemotherapymentioning
confidence: 99%
“…After treatment with an anthracycline or taxane, administration of capecitabine, gemcitabine, and vinorelbine have been found to result in OR rates of 20-25% (Table 2) [20][21][22]. The decision of which single-agent treatment to use in the first-, second-, third-, or fourth-line setting depends on several factors, including patient characteristics, previous treatments, and the expected toxicity of the treatments [15,16,18,19].…”
Section: Single-agent Chemotherapymentioning
confidence: 99%
“…One study demonstrated similar efficacy between 75 mg/m 2 DOX and 90 mg/m 2 EPI. 41 Another trial with analogous design demonstrated similar efficacy with 60 mg/m 2 DOX and 90 mg/m 2 EPI. 42 A third trial compared 60 mg/m 2 of DOX with 85 mg/m 2 of EPI.…”
Section: Epirubicin (Ellence®)mentioning
confidence: 92%
“…Response rates in anthracycline-naïve patients are reported to be in the 25%-50% range [58][59][60][61] . Prior anthracycline exposure, including evaluation of total cumulative dose and other cardiac risk factors (for example, coronary artery disease, prior myocardial infarction, prior mediastinal radiotherapy) necessitate a baseline review of cardiac ejection fraction and monitoring thereafter 62 .…”
Section: Anthracycline and Anthracenedionementioning
confidence: 99%